Research and Development of Energy-storage Light-railVehicle Electric Traction System - CHEN Xin-jian; CHEN Zhong-jie; CHEN Chao-lu; LI Wei; QIAO Xian-hua (机车电传动)
Parameters and performance requirement of energy-storage electric traction light-rail vehicle were introduced. T/B characteristic of electric traction system, simulation and calculation of vehicle operation capability, main circuit, control system and energy-storage management system of the vehicle were expounded. Moreover, energy-storage traction system of the vehicle was compared with traditional electric traction system. The vehicle has passed line routine test and type approval test, which satisfies design requirements.